Analisis Pengembangan Digital Supply Chain (DSC) untuk Pemenuhan Target Produksi pada Perusahaan Minyak Shortening - Nurdien, Ahmad; Kustiwan, Susan; Supriyati, Supriyati (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Industry 4.0 drives supply chain digitalization to enhance operational efficiency. This study analyzes the impact of Digital Supply Chain (DSC) implementation on achieving production targets in a shortening oil company. A quantitative approach with descriptive analysis was used to measure efficiency improvements. Data were collected through observations, interviews, questionnaires, and documentation. The results show that DSC increased operational efficiency by 17%, reduced production downtime by 66.67%, and increased production capacity from 4,650 kg/hour to 5,738 kg/hour. Additionally, DSC contributed to reducing raw material waste and improving production target achievement by 14.76%. Statistical analysis confirmed that DSC significantly affects production efficiency, contributing 80%. This study recommends better system integration and workforce training to maximize DSC benefits.